Bahasa Inggris - Rahmat Kamal (Edukasia Islamika, 2021)
This study aims to: first, describe and analyze the ROHIS Islamic study materials used in SMA Negeri 2 Pemalang; second, formulate the design of Islamic study materials based on the Islamic values ​​of rahmatan lil 'alamin which is needed by ROHIS students at SMA Negeri 2 Pemalang; and third, analyze the effectiveness of using ROHIS Islamic study materials based on Islamic values ​​rahmatan lil 'alamin in the form of book at SMA Negeri 2 Pemalang. Based on the formulation of the first problem, this study used qualitative approach, while based on the formulation of the second and third problems, this study used Research and Development (R&D) approach presented by Borg and Gall. The results showed: (1) ROHIS Islamic Study Materials at SMA N 2 Pemalang consisted of several references, including: the yellow book in the field of fiqh and the material presented by each Islamic study mentor which was not specifically codified in one unity; (2) The formulation of the design of the ROHIS Islamic study material was developed in the formulation of Basic Competence and Indicators which was then developed in the form of the Islamic Book of Rahmatan Lil 'Alamin; and (3) the results of statistical tests using SPSS 18 software showed the average value of the pretest was 47.50 and the posttest was 88.50. Statistical tests were carried out at a significance level of 5%, which resulted in a correlation value of 0.636 which means greater than the significance level of 0.05. (0.636> 0.050) until H0 is rejected. In other words, there is a significant difference in students' understanding of the Islamic values ​​of rahmatan lil 'alamin between before and after using the Rahmatan Lil 'Alamin Islamic Book